Climate Variability, Catastrophic Health Expenditure, and Non-Communicable Disease Outcomes in Nigeria - Jude Igyo Ali; Patricia Lindelwa Makoni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: The challenges posed by climate change and non-communicable diseases (NCDs) are among the most pressing but least explored areas in health economics. Aims: This study examines the impact of climate shocks, non-communicable diseases (NCDs), and catastrophic health expenditure (CHE) in a single micro-econometric model. Methods: The study estimates probit, logit, IV-probit, fixed-effects logit, and IV-2SLS models with temperature anomalies instrumented using the values of the ENSO Oceanic Niño Index to overcome the endogeneity problem, using a harmonized panel of 22,110 households in three waves of the Nigeria General Household Survey-Panel (2010/11, 2012/13 and 2015/16). Results: A 1 °C rise in temperature increases the likelihood of CHE by 4.3-6.1 percentage points and flood vulnerability by 7.1-8.3% points. Across the population affected by non-communicable diseases (NCDs), climate stressors increase the Propensity to experience catastrophic health expenditure (CHE) by approximately 9.4%. Climate variables account for 31.3% of the CHE inequality, with temperature alone explaining 13.6% of the index, and they have a disproportionate impact on poorer households. Instrumental variable projections suggest that an additional 1.9-2.7 million households could experience catastrophic health expenditure (CHE) by 2030 under continued warming trends. Conclusion: Health financing vulnerability in Nigeria is also a function of uneven climate variability, which requires increased health insurance, an enhanced NCD response, and climate-sensitive social protection policies. These results indicate the need for much-needed policy coordination among health, climate, and fiscal governance systems.